Surgeon-conducted color Doppler ultrasound deep inferior epigastric artery perforator mapping: A cohort study and learning curve assessment - Bajus, Adam; Kubek, Tomáš; Dražan, Luboš; Veselý, Jiří; Novák, Adam; Berkeš, Andrej; Streit, Libor (Journal of plastic, reconstructive & aesthetic surgery, 2023)
BACKGROUND: Perforator mapping using diagnostic methods facilitates deep inferior epigastric perforator (DIEP) flap planning. Computed tomographic angiography (CTA) is a well-proven tool for perforator mapping. However, the benefits of color Doppler ultrasonography (CDU) are as follows: 1) CDU involves dynamic real-time examination and 2) does not use radiation. Comparing the accuracies of both methods in a cohort of patients, this study aimed to evaluate the learning curve of surgeon-conducted CDU perforator mapping. METHODS: Twenty patients undergoing DIEP flap breast reconstruction were enrolled in a cohort study. All patients underwent CTA perforator mapping preoperatively. XY coordinates of significant perforators were subtracted by a radiologist. A single surgeon (sonographer) with minimal experience with CDU performed CDU perforator mapping, including XY coordinates subtraction. The sonographer was blinded to the CTA data. The reference coordinates of dissected perforators were measured during surgery. Deviations from reference coordinates for both methods were compared, and CDU mapping learning curve was assessed using Joinpoint Regression. RESULTS: We included 20 women (32 DIEP flaps and 59 dissected perforators). The mean deviation between mapped and reference coordinates was 1.00 (0.50-1.12) cm for CDU and 0.71 (0.50-1.12) cm for CTA. The learning curve of CDU mapping showed the breaking point after the seventh patient (≈ 21 localized perforators). After the breaking point, no significant differences between the deviations of both methods were found (p = 0.980). CONCLUSION: A limited number of examinations were needed for the surgeon to learn CDU DIEA perforator mapping with accuracy similar to that of CTA mapping.
Keywords: Learning Curve; Surgeons; Perforator Flap; kohortové studie; Mammaplasty; Cohort Studies; lidé; Female; Epigastric Arteries; arteriae epigastricae; chirurgové; perforátorový lalok; ultrasonografie dopplerovská barevná; křivka učení; mamoplastika; Ultrasonography, Doppler, Color; ženské pohlaví; Humans